Optimization and short-circuit analysis of photovoltaic penetration in off-grid system – A case study in newmont suriname gold mine - Agustinus, Alpha; Sudiarto, Budi (Universitas Negeri Padang, 2023)
Mining companies are highly dependent on fossil fuels to meet their electricity needs and mining activities such as the use of heavy equipment. Therefore, the greenhouse gas emissions due to burning of fossil fuels have become a major issue related to the impact on the environment due to mining activities. Renewable energy such as Photovoltaic (PV) can be an alternative solution to overcome this problem. This study aims to examine the optimal penetration of Photovoltaic (PV) at Processing Plant Newmont Suriname gold mine. HOMER software is used to design the most optimal Photovoltaic (PV) penetration. ETAP software is used for technical validation through load flow and short-circuit analysis.